Case Report: A middle-aged woman with mediastinal follicular dendritic cell sarcoma complicated by paraneoplastic pemphigus - Wang, Yongchun; Zhou, Min; Wang, Feifei; Hu, Zhiyan; Ruan, Yan (Frontiers in Oncology, 2025)
As a relatively rare malignant entity, follicular dendritic cell sarcoma (FDCS) of the mediastinum currently suffers from insufficient clinical characterization, warranting more comprehensive studies to optimize therapeutic strategies. The initial symptoms of FDCS are often related to the respiratory system. It is particularly rare for the disease to present initially as recurrent ulcers in the oropharynx, which eventually led to a diagnosis of paraneoplastic pemphigus. Here, we report a case of a young female patient diagnosed with mediastinal FDCS associated with paraneoplastic pemphigus. The patient presented with recurrent pharyngeal ulcers and was diagnosed with mediastinal FDCS associated with paraneoplastic pemphigus 10 months later through imaging and pathological examinations.